Nutritional Status and Magnesium Levels in Serum and Urine of Primary Hypertensives and Normotensives - Kayakirilmaz1, Kadriye; Bayol1, Emel; Bal Yilmaz2, Hatice; Ariogul3, Servet (Asian Journal of Chemistry, 2011)
This research has been designed for the determination of the nutritional status, serum and urinary magnesium (UMg) levels and correlation between urinary magnesium and blood pressure (BP). Thirty two volunteers' patients with essential hypertension (HT) and 35 normotensive (NT) control subjects, aged 21-79 years, have participated in this study. Fifty five subjects' 24-h urinary samples were collected (28NT and 27HT). Besides, for determination of the correlation between 24 hUMgV and overnight excretion rate urinary magnesium (12 hUMgV), 43 urine samples were collected. Nutritional status was evaluated according to their food consumption and physical examination. After analyzing the collected blood and urinary samples, the mineral status was also evaluated. Among 13 hypertensive subjects three women had serum magnesium values lower than 1.7 mg Mg/dL (1.38-1.68 %). After 6 months treatment with magnesium, serum magnesium concentrations have increased to normal levels. In both groups blood pressure was positively correlated with UMgV and in hypertension group blood pressure was negatively correlated with serum magnesium levels (p < 0.05). Among the 43 subjects, 12 h UMgV was correlated with the 24 h UMgV and also in normotensive group UMgV was correlated positively with UCaV (p < 0.05). Overnight urinary magnesium excretion rate was correlated with the 24 h UMgV, so 12 h UMgV should be usually employable.